Antitumor Activity of Zinc Nanoparticles Synthesized with Berberine on Human Epithelial Colorectal Adenocarcinoma (Caco-2) Cells through Acting on Cox-2/NF-kB and p53 Pathways - Othman, Mohamed S.; Al-Bagawi, Amal H.; Obeidat, Sofian T.; Fareid, Mohamed A.; Habotta, Ola A.; Moneim, Ahmed E. Abdel (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Drawbacks and side effects of currently available therapies to colorectal cancer (CRC) have compelled researchers to search for new therapeutic strategies. Objective: This study was designed to investigate the effects of zinc nanoparticles biosynthesized with berberine (ZnNPs-BER) on Caco-2 cells compared to 5-Fluorouracil (5-FU) and explore the possible underlying pathways. Methods: Caco-2 and Vero cells were treated with 5-FU, BER, or ZnNPs-BER for 24 h. Cell viability was measured by MTT assay. Oxidative stress and apoptotic markers and cell cycle were determined. Additionally, Cox-2 and NF-kB levels were also measured. Results: The IC50 values of 5-FU, BER, and ZnNPs-BER on Caco-2 cells were found to be 34.65 μM, 19.86 μg/ml and 10.49 μg/ml, respectively by MTT assay. The IC50 value for 5-FU in Vero cells was 21.7 μg/ml, however, BER and BER-ZnNPs treatment showed non-toxic effects on the Vero cells. Further, ZnNPs-BER exerted significant induction of ROS besides exhaustion of the antioxidant capacity of tumor cells indicated by a decline in GSH and elevated NO and MDA contents. Marked increments in levels of Bax and caspase-3 were detected together with declines in Bcl- 2 levels in Caco-2 cells subjected to BER-ZnNPs therapy. On the molecular basis, upregulation in mRNA levels of pro-apoptotic genes (Bax, caspase-3, and tumor suppressor gene p53) along with downregulation in the anti-apoptotic gene (Bcl-2) were observed in ZnNPs-BER treated Caco-2 cells. Furthermore, ZnNPs-BER showed more pronounced effects on apoptosis increased cell percentage in the S and subG1 phases. In addition, green synthesis of ZnNPs with BER showed notable induction of Cox2 and NF-kB in Caco-2 cells. Conclusion: Therefore, the antitumor potential of ZnNPs-BER in colon cancer cells may be endorsed for induction of oxidative stress, inflammation, and apoptotic changes in tumor cells. Our study documents the therapeutic potential of Zn nanoparticles conjugated with BER, which may be a new option for combined chemotherapy.
Keywords: Zinc nanoparticles